Fenomena Kemiskinan Masyarakat Nelayan dan Interelasi Pemahaman Keagamaan (Studi pada Masyarakat Nelayan di Teluk Buo Kelurahan Teluk Kabung Tengah Kecamatan Teluk Kabung Kota Padang) - muhammad Fauzi (Al-Hikmah: Jurnal Dakwah dan Ilmu Komunikasi, 2019)
Various studies of poverty have given rise to different perspectives on poverty as a real phenomenon in people's lives. The focus of this study is on problems; a). what are the causes of poverty in the fishing community of Teluk Buo, Teluk Kabung Tengah Village, Bungus Teluk Kabung District, Padang City; b) what forms of poverty the fishing community of Teluk Buo, Teluk Kabung Tengah Village, Bungus Teluk Kabung District, Padang City; and c) how the religious understanding of the Bungus Teluk Kabung fishing community about work motivation. To answer this problem, qualitative research methods are used. Collect data by surveying, observing and interviewing.Poverty can not only be seen from an economic perspective, but can be seen in other very broad perspectives such as: cultural, traditional, religious and religious sides. Poverty experienced by fishing communities is not only due to low income, but also due to the value system factors that influence it. For the Buo Bay fishing community Teluk Kabung Village, for example, the spirit of religion to do spirit and motivation does not